Modal analysis of the human tympanic membrane of middle ear using the finite-element method - Skrodzka, E.; Modławska, J. (Archives of Acoustics, 2006)
This paper provides a theoretical vibrations model of tympanic membrane constructed and solved using the finite-element method. This method is an appropriate tool to analyze the middle-ear vibrations because it enables modeling in details the complicated shape of the middle-ear and, moreover, and allows to calculate the distribution of vibrations stimulated by sinusoidal signals. The number of the 3-dimensional tetrahedral elements was assumed to be 591 and material properties used were based on data available in the literature. This model has a uniform density of 1.2 · 10^3 kg/m^3, an area of 70· 10^−6 m^2, a depth of 1.54 · 10^−3 m at the umbo, a mean thickness of 1.32 · 10^−4 m, and a Poisson’s ratio 0.3. Constrains were accomplished by two different springs, linear and torsional. The results obtained are compared with their counterparts scattered in the literature.